Synthesis , Characterization and Study of Biological Activity of Some New Schiff Bases ,1,3-Oxazepine and Tetrazole Derived from 2,2 di thiophenyl Acetic Acid - Hussain, Eman M.; Naji, Hussam Z. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
In this study new derivatives of Schiff bases 5-8 , 1,3- oxazepine 9-16 and tetrazoles 17-19 have been synthesized from the new starting material 1 which has synthesized the reaction of one mole of dichloro acetic acid and two moles of thiophenol , the esters 2-3 were synthesized from the reaction of compound 1 with methanol or ethanol respectively in the presence of H2SO4 as catalyst then 2,2-dithiophenylaceto Hydrazide 4 were synthesized from the reaction of 2 or 3 with hydrazine hydrate 80 % , Schiff bases 5-8 were synthesized from the reaction of 4 with appropriate aldehyde or ketone .Treatment of Schiff bases with maleic and phathalic anhydride in dry benzene to give 1,3-oxazepen derivatives 9-16 and with sodium azide in tetrahydrofuran (THF) afforded tetrazole derivatives 17-19. All these compounds have been characterized from their melting pointes, FTIR , 1HNMR and compounds 1,5 and 18 by mass spectrometry . Derivatives 6,7,11,16,17 and 18 were tested against inhibition of E.coli and. Staphylococcus- aureus and were all funds to be active. Scheme (1).